Epidermotropism of inflammatory cells differentiates pyoderma gangrenosum from venous leg ulcers - Ronicke, Moritz; Baur, Andreas; Kirr, Michael; Erdmann, Michael; Erfurt-Berge, Cornelia; Ostalecki, Christian (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Background and objectives Pyoderma gangrenosum is an ulcerative autoinflammatory disease, lacking distinct histopathological characteristics to differentiate from other ulcerating conditions, like venous leg ulcers. The objective of this study was therefore to find histopathological characteristics of pyoderma gangrenosum in a head-to-head comparison to venous leg ulcers. Patients and methods Eight tissue samples of pyoderma gangrenosum, twelve samples of venous leg ulcers and six samples of healthy skin were stained using an immunohistological multi antigen staining technology. The immune infiltrate and its spatial distribution were analyzed with contextual tissue cytometry software using fluorescence images. Results The dense epidermal presence of CD45RO(+) memory T cells and the rarefication of CD1a(+) Langerhans cells in the epidermis were defining markers for pyoderma gangrenosum, implicating an epidermal immune reaction. In addition, high numbers of CD11c(+)CD68(+) pro-inflammatory M1 macrophages were detected in the dermis, significantly extending the numbers seen in venous leg ulcers. Conclusions The histopathological differences found between pyoderma gangrenosum and venous leg ulcer can be used to distinguish between the two diseases and thus provide an important aid for the rapid initiation of adequate therapy. In addition, our data hint at an antigen-driven process in the epidermis, possibly involving CD1a(+) Langerhans cells.
CRIS-Team WoS Importer:2022-05-13